Selecting Patients for Lobar Lung Volume Reduction Therapy: What Quantitative Computed Tomography Parameters Matter? - Theilig, Dorothea Cornelia; Huebner, Ralf-Harto; Neumann, Konrad; Poellinger, Alexander; Doellinger, Felix (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Purpose Evaluation of emphysema distribution with quantitative computed tomography (qCT) prior to endoscopic lung volume reduction (ELVR) is recommended. The aim of this study was to determine which of the commonly assessed qCT parameters prior to endoscopic lung volume reduction (ELVR) best predicts outcome of treatment.Materials and Methods 50 patients who underwent technically successful ELVR at our institution were retrospectively analyzed. We performed quantitative analysis of the CT scans obtained prior to ELVR and carried out Mann-Whitney U-tests and a logistic regression analysis to identify the qCT parameters that predict successful outcome of ELVR in terms of improved forced expiratory volume in 1 second (FEV1).Results In the Mann-Whitney U-test, the interlobar emphysema heterogeneity index (p = 0.008) and the pulmonary emphysema score (p = 0.022) showed a statistically significant difference between responders and non-responders. In multiple logistic regression analysis only the interlobar emphysema heterogeneity index (p = 0.008) showed a statistically significant impact on the outcome of ELVR, while targeted lobe volume, total lung volume, targeted lobe emphysema score and total lung emphysema score did not.Conclusion Of all commonly assessed quantitative CT parameters, only the heterogeneity index definitely allows prediction of ELVR outcome in patients with advanced chronic obstructive pulmonary disease (COPD).Key Points Citation Format
Keywords: CT-quantitative; chronic obstructive pulmonary disease; lung volume reduction therapy